Effects of Antioxidants in Human Milk on Bronchopulmonary Dysplasia Prevention and Treatment: A Review - Yang, Xianpeng; Jiang, Shanyu; Deng, Xianhui; Luo, Zichen; Chen, Ailing; Yu, Renqiang (Frontiers in Nutrition, 2022)
Bronchopulmonary dysplasia (BPD) is a severe chronic lung illness that affects neonates, particularly premature infants. It has far-reaching consequences for infant health and their families due to intractable short- and long-term repercussions. Premature infant survival and long-term quality of life are severely harmed by BPD, which is characterized by alveolarization arrest and hypoplasia of pulmonary microvascular cells. BPD can be caused by various factors, with oxidative stress (OS) being the most common. Premature infants frequently require breathing support, which results in a hyperoxic environment in the developing lung and obstructs lung growth. OS can damage the lungs of infants by inducing cell death, inhibiting alveolarization, inducing inflammation, and impairing pulmonary angiogenesis. Therefore, antioxidant therapy for BPD relieves OS and lung injury in preterm newborns. Many antioxidants have been found in human milk, including superoxide dismutase, glutathione peroxidase, glutathione, vitamins, melatonin, short-chain fatty acids, and phytochemicals. Human milk oligosaccharides, milk fat globule membrane, and lactoferrin, all unique to human milk, also have antioxidant properties. Hence, human milk may help prevent OS injury and improve BPD prognosis in premature infants. In this review, we explored the role of OS in the pathophysiology of BPD and related signaling pathways. Furthermore, we examined antioxidants in human milk and how they could play a role in BPD to understand whether human milk could prevent and treat BPD.